From modernity to dependency theories poverty still remains in Africa: which way now? - Matunhu, Jephias (Mambo Press, 2016)
Poverty is Africa’s greatest challenge. Seemingly, the continent’s anti-poverty strategies have failed. A basket of reasons explain this failure. Chief among them is that Africa’s anti-poverty strategies were and are still being informed by wrong theoretical foundations. The Modernization and the Dependence theories, among others have failed to heave Africa out of poverty. Now which way for Africa a continent that is endowed with rich resources like oil, minerals, land, forestry, scenery and human capital? This paper, pins hope on the African Renaissance theory of development.